Antimicrobial and anti-oxidant activities of quinoline alkaloids from Pseudomonas aeruginosa BCC76810 - Supong, Khomsan; Thawai, Chitti; Supothina, Sumalee; Auncharoen, Patchanee; Pittayakhajonwut, Pattama (My University, 2016)
Twelve 4-hydroxyquinoline derivatives (1–12) and three phenazine alkaloids (13–15) have been isolated from Pseudomonas aeruginosa BCC76810. All these compounds, except compounds 6, 7, 9, and 11, are known. The new quinolines are 2-((Z)-undec-4′-enyl)-4-hydroxyquinoline (6), 2-(3′-(2′-hexylcyclopropyl)propyl)-4-hydroxyquinoline (7), 2-n-octyl-4-hydroxyquinoline N-oxide (9), and 2-((Z)-undec-4′-enyl)-4-hydroxyquinoline N-oxide (11). Their structures were elucidated based on the spectroscopic information, such as 1D, 2D NMR, UV, and HRESIMS data. 4-Hydroxyquinolines (1–6) and 4-hydroxyquinoline-N-oxides (8–11) exhibited antimalarial activity against Plasmodium falciparum, K1 strain (IC50 0.25–2.07 μg/mL) with moderate to weak cytotoxicity against cancerous (KB, MCF-7, NCI-H187) and non-cancerous (Vero) cells. In addition, 4-hydroxyquinoline N-oxides also displayed anti-Bacillus cereus and antioxidant activities.
Keywords: Anti-oxidant; Antimicrobial; Oryza saltiva; Pseudomonas; Quinolines; Rice